Mosquito vector diversity and malaria transmission - St. Laurent, Brandy (Frontiers in Malaria, 2025)
Malaria is the most important parasitic disease in the world, killing over half a million people a year. Globally, we have made gains toward eliminating this disease but our progress has stalled in the last decade. Much of our control efforts and predictive models are focused to a few well understood systems such as Plasmodium falciparum transmission by species within the Anopheles gambiae complex. However, in many areas of the world, variation in the diversity of mosquito vectors significantly shape malaria transmission dynamics, seasonal persistence, and geographic range. This perspectives piece will focus on vectors of human malaria parasites and the impact of vector diversity on disease transmission by exploring how: 1) Anopheles species richness and abundance influence daily malaria transmission, and how differences in host feeding behavior and vector competence within a species-rich vector community influence local transmission, 2) diverse species contribute to persistence of malaria across seasons and spread through different ecotypes, and 3) species-specific parasite-vector interactions determine the genotypes of the malaria parasite that are successfully transmitted and shape parasite population structure. Finally, we will discuss future areas of research that should be prioritized toward understanding a more complete picture of malaria transmission dynamics in the context of diverse vector species.